Marginal Deterrence at Work - Rosario Crinò; Giovanni Immordino; Salvatore Piccolo (Center for Economic Studies and ifo Institute (CESifo), 2017)
We test the rational economic model of marginal deterrence of law enforcement - i.e., the need for graduating the penalty to the severity of the crime. We combine individual-level data on sentence length for a representative sample of US inmates with proxies for maximum punishment and monitoring costs across US states over 50 years. Consistent with the theory of marginal deterrence, we show that sentence length is increasing in maximum penalty and decreasing in monitoring cost. We also provide evidence that steeper sanctions are associated with less severe crimes, consistent with marginal deterrence being eective. Overall, these findings favor the marginal deterrence framework over competing theories of justice.
Keywords: K14; K40; 330; marginal deterrence; enforcement policies; individual-level data; death penalty